Oceanomania: souvenirs of mysterious seas: from the expedition to the aquarium- A Mark Dion Project - Basta, Sarina; Dion, Mark; Raimondi, Cristiano (Villa Paloma/Nouveau Musee National de Monaco, 2011)
Exhibition catalog.
English
Keywords: N4390-5098 Visual Arts. Exhibitions